Simultaneous Treatment with P53 Overexpression and Interferon Î³ Exerts a Dramatic Increase in Apoptosis Induction of U87 Cells - Abbasy, Zahra; Zaferani Arani, Hamid; Ale-Ebrahim, Mahsa; Moodi, Vihan; Nematian, Javad; Barati, Mojdeh; Shafaie, Saba; Madjid Ansari, Alireza; Hashemi, Atousa; Davoodi, Poorya; et al. (Galen Medical Journal, 2021)
Background: Gliomas possess low immunogenicity, which is an inevitable hinder in front of cancer immunotherapy. Different interferons (IFNs) may proceed apoptosis instead in p53-dependent or independent pathways. P53 induces the anti-inflammatory programmed cell death in cancer cells; on the other hand, IFN gamma (IFNÎ³) is a modulatory/pro-inflammatory cytokine. There are contradictory reports of whether this cytokine can possess an anti- or pro-cancerous impact on tumors. Hence, we aimed to investigate the possible cooperative apoptotic effect of the P53 and IFNÎ³ over expressions on the U87 glioblastoma cell line. Materials and Methods: The P53 expressing vector was amplified by Escherichia coli BL21. This vector was confirmed by the aid of sequencing. At the next step, U87 cells were transfected using lipofectamine. Cells were treated with P53 vector and/or IFNÎ³. The type of cellular death investigated by flow cytometry and the expression level of cleaved caspase-3 protein was also precisely demonstrated by western blotting. Results: Sequencing results revealed that inserted P53 was identical with human P53. Western blot results revealed that both IFNÎ³ and P53 overexpression could up-regulate cleaved caspase-3 protein expression in this cell line. Interestingly, flow cytometry data determined that concurrent treatment with P53 exogenous overexpression and IFNÎ³ induces about 70% apoptosis in U87; more than the sum of cell death occurs after IFNÎ³ or P53 overexpression alone ( 18%+21%=39%). Conclusion: The present study results showed that p53-overexpression and IFNÎ³ could ultimately induce up-regulation of the caspase-3 and ultimately significant apoptosis increasing in the U87 cell line. Although IFNÎ³ is believed to be a pro-inflammatory cytokine and P53 is an anti-inflammatory agent, our results demonstrated that they could act synergistically to induce apoptosis in U87 cells. [GMJ.2021;10:e2270]